2005
DOI: 10.1111/j.1365-2605.2005.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of experimental testicular torsion

Abstract: We investigated the feasibility of contrast enhanced (CE)-dynamic magnetic resonance imaging (MRI) for the detection of testicular torsion induced hypoperfusion in an experimental rat model. Adult Sprague-Dawley rats were subjected to unilateral testicular torsion of 360 or 720 degrees. After 1 h, the tail veins of the anaesthetized rats were cannulated and T2 -, diffusion-weighted and T1-weighted CE-dynamic MRI were subsequently performed by a 1.5 T MRI scanner. On apparent diffusion coefficient (ADC) images,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…For these reasons, it has limited use. Diffusion weighted imaging has been shown to be a successful method in the diagnosis of complete TT in the early period [ 5 , 18 ]. However, to the best of our knowledge, the role of DWI in partial testicular torsion in the early stage has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it has limited use. Diffusion weighted imaging has been shown to be a successful method in the diagnosis of complete TT in the early period [ 5 , 18 ]. However, to the best of our knowledge, the role of DWI in partial testicular torsion in the early stage has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…In rat testes, in vivo scans at lower field strengths (4.7T) show tubular structure in T2 weighted images with scan times of 68 minutes or less (5). Even lower field strengths (1.5T) have successfully been used in rats to detect hypoperfusion following experimental testicular torsion using scan sequences lasting less than 10 minutes (5, 21). This, combined with our high-resolution structural images in situ, strongly suggests that high field strength MRI is both feasible and useful when investigating murine testes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…MRI/MRS may also be valuable clinical tools. For example, MRI can be used in humans to visualise intratesticular lesions (22-24), testicular tumours (25), torsion (21, 26), varicoceles (27, 28) and testicle location (29) at common clinical MR field strengths. Reduction in testicular size, epididymis diameter or seminiferous tubule diameter (30) may be markers of disrupted spermatogenesis, and the size of either could thus potentially be used as an indicator of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is another method that can be done with or without contrast enhancement 28. In an experimental study, it was stated that torsion caused ipsilateral hypoperfusion, resulting in decreased gadolinium uptake on MRI 29. It was reported that contrast‐enhanced subtraction MRI could provide information about testicular perfusion in testicular torsion, which shows no or little contrast enhancement regarding hemorrhagic necrosis 30.…”
Section: Discussionmentioning
confidence: 99%